PENERAPAN MODEL TREFFINGER UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK KELAS XI FASE F DI MAN 1 PASAMAN BARAT - Aurina, Hifzil; Emiliannur, Emiliannur; Winarmo, Nanang (Universitas Negeri Malang, 2025)
The Science and technology in the 21st century demands an increase in the quality of education according to the current curriculum, namely the independent curriculum. The independent curriculum is made into two elements of skills, namely the process and understanding of concepts. The background of this study is the low level of students' creative thinking skills. This happens because learning still uses a direct (conventional) learning model. The solution used to improve students' creative thinking skills is to use the Treffinger model. This study aims to determine the effect of the Treffinger model on students' creative thinking skills. This type of research is quantitative research or experimental research. The subjects of the study were students of class XI Phase F MAN 1 West Pasaman. The sampling technique of the study used simple random sampling, which was done randomly without considering the strata in the population. The instrument used in this study was a creative thinking ability test with a posttest only design. The data analysis techniques used were normality test, homogeneity test, validity test, reliability test, discriminatory power test, difficulty level test and hypothesis test. Based on the research that has been conducted, data on students' creative thinking abilities at a significance level of 0.05 showed results below 0.05, which means that the proposed hypothesis is accepted. The results of the analysis indicate that the Treffinger learning model has a significant influence on students' creative thinking abilities. This can be seen from the increasing competence of students' creative thinking abilities (cognitive).